Embedding Indigenous knowledge in the curriculum: Principles and strategies across the Australian higher education sector - Seb Dianati; Reuben Bolt (The Australian Journal of Indigenous Education)
In this paper we document the various strategies universities have undertaken or are currently undertaking in their Indigenising practices across the Australian higher education sector by screening university websites for their strategies, principles and initiatives. It serves as a vital stocktake, audited in November 2023, for institutions aiming to forge a path towards an inclusive and culturally diverse academic environment. While such benchmarks should be tempered with caution due to the diversity of First Nations communities in which universities operate, it offers a spectrum of current practices for further development and growth. At the same time, it reinforces the current transition, from the perspective of Western science, of the value of Indigenous knowledges, epistemologies and approaches within the curriculum.